Haplotype mining panel for genetic dissection and breeding in Eucalyptus. (21st December 2022) - Candotti, Julia; Christie, Nanette; Ployet, Raphael; Mostert‐O'Neill, Marja M.; Reynolds, S. Melissa; Neves, Leandro Gomide; Naidoo, Sanushka; Mizrachi, Eshchar; Duong, Tuan A.; Myburg, Alexander A.
SUMMARY: To improve our understanding of genetic mechanisms underlying complex traits in plants, a comprehensive analysis of gene variants is required. Eucalyptus is an important forest plantation genus that is highly outbred. Trait dissection and molecular breeding in eucalypts currently relies on biallelic single‐nucleotide polymorphism (SNP) markers. These markers fail to capture the large amount of haplotype diversity in these species, and thus multi‐allelic markers are required. We aimed to develop a gene‐based haplotype mining panel for Eucalyptus species. We generated 17 999 oligonucleotide probe sets for targeted sequencing of selected regions of 6293 genes implicated in growth and wood properties, pest and disease resistance, and abiotic stress responses. We identified and phased 195 834 SNPs using a read‐based phasing approach to reveal SNP‐based haplotypes. A total of 8915 target regions (at 4637 gene loci) passed tests for Mendelian inheritance. We evaluated the haplotype panel in four Eucalyptus species ( E. grandis, E. urophylla, E. dunnii and E. nitens ) to determine its ability to capture diversity across eucalypt species. This revealed an average of 3.13–4.52 haplotypes per target region in each species, and 33.36% of the identified haplotypes were shared by at least two species. This haplotype mining panel will enable the analysis of haplotype diversity within and between species, and provide multi‐allelic markers that can be used for genome‐wide association studies and gene‐based breeding approaches. Significance Statement: We developed a haplotype sequencing panel for Eucalyptus targeting 8915 regions at 4637 gene loci associated with growth and wood properties, pest and disease resistance, and abiotic stress response providing a genome‐wide, multi‐allelic, gene‐centric genotyping resource for eucalypts. We tested the panel in four Eucalyptus species ( E. grandis, E. dunnii, E. nitens and E. urophylla ), and found an average of 3.65 haplotypes per target region per species, and 9.98 across all four species.